Compositional dynamics of multilevel innovation platforms in agricultural research for development - Lamers, D.; Schut, Marc; Klerkx, Laurens; Asten, Piet J.A. van (Oxford University Press, 2017)
Innovation platforms (IPs) form a popular vehicle in agricultural research for development (AR4D) to facilitate stakeholder interaction, agenda setting, and collective action toward sustainable agricultural development. In this article, we analyze multilevel stakeholder engagement in fulfilling seven key innovation system functions. Data are gathered from experiences with interlinked community and (sub)national IPs established under a global AR4D program aimed at stimulating sustainable agricultural development in Central Africa. Our findings show that all innovation systems functions required multilevel action, but that fulfillment of specific functions demands for strategic involvement of specific stakeholders at specific levels. We observed that a research- and dissemination-oriented sequence in the functions was prioritized in AR4D IPs and argue that such a sequence may be different in other types of (business) IPs. Our findings provide an incentive to think function oriented about compositional dynamics (stakeholder groups * levels) in innovation processes, rather than striving for equal stakeholder participation.